METHODS OF SEISMIC LOADS DECREASING DURING BUILDING RECONSTRUCTION - Pershakov, Valeriy; Gyrych, Victoria; Grebenyuk, Olena; Scalova, Daria; Fesh, Alla (Proceedings of National Aviation University (archive), 2006)
Classification of existent buildings by their ability to resist seismic impact is needed in order to improve antiseismic qualities of existent buildings and constructions. The improvement of antiseismic properties can be attained by realization of certain strategy. The example of a building reconstruction with multispan coverage is presented.